Advanced magneto-optical Kerr effect measurements of superconductors at low temperatures - Claudia Stahl; Joachim Gräfe; Stephen Ruoß; Patrick Zahn; Jonas Bayer; Julian Simmendinger; Gisela Schütz; Joachim Albrecht (AIP Advances, 2017)
Magneto-optical Kerr-effect (MOKE) measurements of superconducting films with soft-magnetic coatings are performed at low temperatures using a laser-based MOKE set-up. An elaborate measurement scheme with internal reference allows the quantitative comparison of the temperature dependent Kerr-amplitude with the magnetic field generated by supercurrents. For this purpose, an amorphous CoFeB thin film exhibiting a large Kerr-signal is deposited directly on top of the YBCO superconductor acting as field sensing layer. It is shown that the resulting magnetic hysteresis loops of the soft-magnetic film can be used to reconstruct the electric properties of the superconductor.